ANALISIS EFEKTIVITAS PENGGUNAAN ANTIBIOTIKA PADA PASIEN SIROSIS HEPATIS DENGAN KOMPLIKASI SPONTANEOUS BACTERIAL PERITONITIS DI SALAH SATU RUMAH SAKIT DI YOGYAKARTA - Adnan Adnan; Lolita Lolita (Sekolah Tinggi Ilmu Kesehatan ISFI Banjarmasin, 2020)
Cirrhosis is a diffusion process characterized by fibrosis and changes from normal hepatic structures to structurally abnormal nodules. In general, complications that often occur in hospitalized patients are Spontaneous Bacterial Peritonitis (SBP). Many antibiotic therapies can be used for SBP, for example aminoglycosides, third-generation cephalosporins, penicillins, quinolones and sulfa groups. The purpose of this study was to determine whether there are differences in the effectiveness of antibioics used in SBP therapy. This type of research is observational analytic with cross sectional approach. Retrospective data collection in patients with cirrhosis of the liver with SBP complications in PKU Muhammadiyah Yogyakarta Hospital in 2018. Samples are all patients with cirrhosis of the liver with SBP complications who meet the inclusion and exclusion criteria. The sampling method is purposive sampling. The data taken is demographic characteristic data and clinical characteristics. Analysis of the data used in this study is multivariate analysis and different tests. There were 30 samples that met the criteria with a composition of 18 men (60%) and 12 women (40%). There were 8 people who received ceftriaxone antibiotics and 22 people got cefotaxime therapy.